Analisis Kesulitan Membaca Permulaan pada Siswa Kelas 1 Madrasah Ibtidaiyah Mahad Al-Zaytun Kabupaten Indramayu - Norma Yunita Sila; Anjar Sulistyani; Henri Peranginangin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This study aims to analyze the results of the reading difficulties of the first graders of Madrasah Ibtidaiyah Al-Zaytun, Indramayu Regency. This research is a descriptive research with a quantitative approach. The population in this study were all grade 1 students of MI Al-Zaytun. The sampling technique used in this study is a purposive sampling technique, that is chosen with certain considerations and objectives. The students who became the sample were class 1-B-05. Collecting data using test techniques, observation, interviews and documentation. Data analysis used non-statistical analysis. The research process begins by giving a reading test to students, then after the aspect of reading difficulties is known, Then observed the characteristics of students who have reading difficulties. The results showed that of the 23 students in class 1-B-05, 16 out of 23 students had low scores on one or more aspects of reading. The aspect of the students' highest difficulty in beginning reading is (1) have not been able to read double consonants with a score of 22%. 2) have not been able to read double vowel words with a score of 31%. (3) reading combined vowel-consonant words with a score of 40% and (4) the last difficulty aspect is reading consonant-vowel-consonant combined words with a score of 47%. The characteristics of students' initial reading difficulties are: (1) omission of letters/words, (2) incorrect word pronunciation, (3) letter reversal and (4) hesitation or halting in reading.Keywords: Reading; Beginning Reading; Beginning Reading Difficulty AbstrakPenelitian ini bertujuan untuk menganalisis hasil kesulitan membaca permulaan siswa kelas 1 Madrasah Ibtidaiyah Al-Zaytun Kabupaten Indramayu. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh siswa kelas 1 MI Al-Zaytun. Teknik sampling yang digunakan dalam penelitian ini adalah teknik purposive sampling, yaitu dipilih dengan pertimbangan dan tujuan tertentu. Siswa yang menjadi sampel yaitu kelas 1-B-05. Pengumpulan data menggunakan teknik tes, observasi, wawancara dan dokumnetasi. Analisis data menggunakan analisis non-statistik. Proses penelitian ini dimulai dengan memberikan tes membaca kepada siswa, kemudian setelah aspek kesulitan membaca diketahui, lalu diamati karakteristik siswa yang mengalami kesulitan membaca tersebut. Hasil penelitian menunjukkan bahwa dari 23 siswa di kelas 1-B-05, terdapat 16 dari 23 siswa memiliki skor yang rendah pada satu atau lebih aspek membaca. Aspek kesulitan tertinggi siswa dalam membaca permulaan adalah (1) belum mampu membaca kata konsonan rangkap dengan skor 22%. (2) belum mampu membaca kata vokal rangkap dengan skor 31%. (3) membaca kata gabungan vokal-konsonan dengan skor 40% dan (4) aspek kesulitan terakhir yaitu membaca kata gabungan konsonan-vokal-konsonan dengan skor 47%. Karakteristik kesulitan membaca permulaan siswa yaitu: (1) penghilangan huruf/kata, (2) pengucapan kata salah, (3) pembalikkan huruf dan (4) ragu-ragu atau tersendat-sendat dalam membaca.Kata Kunci: Membaca; Membaca Permulaan; Kesulitan Membaca Permulaan